Electrode modification based on click electrochemistry between terminal-alkynyl substituted cobalt phthalocyanine and 4-azidoaniline - KOCA, ATIF (ELSEVIER SCIENCE SA, 2014)
A new electrochemical sensor electrode was constructed with a new electrode modification technique, click electrochemistry (CEC) based on a functional cobalt phthalocyanine. In this newly constructed modified electrode (GCE/PANI-N-3/ITA-CoPc (CEC)), a terminal-alkynyl (TA) substituted cobalt phthalocyanine (CoPc-TA) was electrochemically bonded to the azido end of electro-polymerized 4-azidoaniline (PANI-N-3), which was electropolymerized on the GCE electrochemically previously. GCE/PANI-N-3/TA-CoPc (CEC) electrode was characterized with voltammetric, electrochemical impedance spectroscopy (EIS), UV-vis spectroscopy, and scanning electron microscopy (SEM) techniques. GCE/PANI-N-3/TA-CoPc electrode gave three redox couples assigned to the CoPc and PANI in nonaqueous and aqueous electrolyte systems, which is a desired factor for the application of a modified electrode in various electrochemical applications such as electrocatalytic and electrosensing fields. Pesticide sensing responses of GCE/PANI-N-3/TA-CoPc (CEC) electrode were tested with SWV method for usability as an electrochemical pesticide sensor for eserine. Basic sensor parameters, calibration lines, and detection limits (LOD) of GCE/PANI-N-3/TA-CoPc (CEC) electrode were derived from SWV responses of the electrode. Amperometric sensing analyses of SVW responses of the electrode give a linear range between 1.56 x 10(-7) and 2.45 x 10(-6) mol dm(-3) eserine with a sensitivity of 1.15 A dm(3) mol(-3) and LOD of 1.75 x 10(-7) mol dm(-3) (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Electrochemistry; Modified electrode; Click electrochemistry; Electropolymerization; CHEMICALLY-MODIFIED ELECTRODES; WALLED CARBON NANOTUBES; IN-SITU; ELECTROCATALYST SYSTEM; VOLTAMMETRIC BEHAVIOR; HYDROGEN-PEROXIDE; DISSOLVED-OXYGEN; PASTE ELECTRODE; ITO ELECTRODE; THIN-FILMS